Accurate and sensitive determination of hydroxychloroquine sulfate used on COVID-19 patients in human urine, serum and saliva samples by GC-MS - Süleyman Bodur; Sezin Erarpat; Ömer Tahir Günkara; Sezgin Bakırdere (Elsevier, 2021)
A rapid, accurate, and sensitive analytical method, ultrasonication-assisted spraying based fine droplet formation-liquid phase microextraction-gas chromatography-mass spectrometry (UA-SFDF-LPME-GC-MS), was proposed for the determination of trace amounts of hydroxychloroquine sulfate in human serum, urine, and saliva samples. To determine the best extraction strategy, several liquid and solid phase extraction methods were investigated for their efficiencies in isolation and preconcentration of hydroxychloroquine sulfate from biological matrices. The UA-SFDF-LPME method was determined to be the best extraction method as it was operationally simple and provided accurate results. Variables such as the extraction solvent, spraying number, sodium hydroxide concentration and volume, sample volume, mixing method, and mixing period were optimized for the proposed method using the one-variable-at-a-time approach. In addition, Tukey's method based on a post hoc comparison test was employed to evaluate the significant difference between the parameters inspected. After the optimization studies, the limit of detection (LOD) and limit of quantification (LOQ) were determined to be 0.7 and 2.4 μg/kg, respectively. The sensitivity of the GC-MS system based on the LOD was enhanced approximately 440-fold when the UA-SFDF-LPME method was employed. Spiking experiments were also conducted for the human serum, urine, and saliva samples to determine the applicability and accuracy of the proposed method. Recoveries for the human serum, urine, and saliva samples were found to be in the ranges of 93.9%-101.7%, 95.2%-105.0%, and 93.1%-102.3%, respectively. These results were satisfactory and indicated that the hydroxychloroquine sulfate level in the above biological samples could be analyzed using the proposed method.